Aerospace series. Cables, electrical, for general purpose. Operating temperatures between -55 °C and 200 °C. DRP (pair) DRT (3 cores) DRQ (4 cores) family, multicore UV laser printable jacketed cable. Product standard Part 008, (5th December 2022) - British Standards Institution,
No abstract available